Effect of Ketip Banana (Musa paradisiaca Forma typiaca) Peel Ethanol Extract on Sperm Viability of Mice (Mus musculus) Following Cigarette Smoke Exposure - Bahri, Syamsul (Jurnal Biologi Tropis, 2024)
Tobacco smoke contains more than 4000 kinds of constituents, including nicotine, tar, carbonic monoxide, polycyclic aromatic hydrocarbons, and heavy metals. Because of the complexity of tobacco smoke components, the toxicological mechanism is notably complicated. Most studies have reported reduced semen quality, reproductive hormone system dysfunction and impaired spermatogenesis, sperm maturation, and spermatozoa function in smokers compared with nonsmokers. Many studies have reported plant tissue contain secondary metabolites such as saponin, terpenoid, alkaloid, and flavonoid with antioxidant properties. Tropical fruit species that is known rich antioxidants content is banana, and one cultivar  banana is Ketip. The aim of this research is to study the effect of Ketip banana peel  ethanol extract on sperm viability of mice following cigarettes exposure. Data analysis showed that tobacco smoke exposure tend to dccrease sperm viability but insignificantly. Treatment with ethanol extract of ketip banana tend to reduce sperm viability. It is concluded that ethanol extract of ketip banana insignificantly increase sperm viability.